Mailbox - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
We got mail, you got mail! - this time from and about readers in four ACP regions - including one from our growing number of correspondents in Haïti. Welcome all, especially to an 'outsider' from east Asia. Does it matter where you're from when we know w